Effect of switching force control direction on consecutive compared to discrete adjustment - Chiaki Ohtaka; Motoko Fujiwara (Japanese Society of Physical Fitness and Sports Medicine, 2019)
We investigated the characteristics of consecutive adjustment focusing on the phase before relaxing completely compared to discrete adjustment that involves just relaxing completely. Eleven participants were instructed to produce an isometric knee extension force based on their maximum voluntary force (MVF), as quickly and accurately as possible. They conducted discrete and consecutive tasks. For the discrete task, they were asked to relax their force completely from a starting level of 20% or 60% MVF. And for the consecutive task, they were asked to match the target level of 20%, 40%, or 60% MVF after they completely relaxed their force from the starting level of 20% or 60% MVF. Produced force was recorded, and the parameters of quickness (onset time, relaxation time, and rate of force development) were analyzed. Relaxation time was slower in consecutive adjustment than in discrete adjustment in the case of the 20% starting level. On the other hand, the onset time was constant irrespective of the process of adjustment. Our results indicated that the process of consecutive adjustment affects the relaxation time in the case of force control.